Nilai Tukar Berpengaruh terhadap Pinjaman Luar Negeri Indonesia, 1997-2007 - Yerimias Manuhutu (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2010)
The main objective of this paper is to evaluate the impact of exchange rate to government external fund. Data used in this research originated from Financial Depatment (Depkeu) and Central Bank Of Indonesia (BI). Using VAR equation model to esimate this research.The result of the study shows that result of Granger causality test that happened the one way relation namely exchange rate (ER) influences government fund loan (GFL). Result of IRF indicates that variable of exchange rate have a big effect on GFL and composition from GFL influenced by innovation of itself and at period hereinafter the exchange rate give big influence. Keywords: exchange rate, government fund loan, vector autoregression